Implementasi Strategi Manajemen Pemasaran Fire Product dalam Optimalisasi Distribusi Rantai Pasok di PT. Amman Mineral Nusa Tengara Barat - Fajar Ramadhan Tidar; Ady Setiawan; Rukin Rukin (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze the implementation of Fire Product marketing management strategies in optimizing supply chain distribution at PT. Amman Mineral Nusa Tenggara Barat. An exploratory case study with a qualitative approach was conducted through semi-structured interviews, participatory observation, and documentation studies involving 20 key informants from various departments. The results show that PT. Amman Mineral implements multi-dimensional marketing strategies with a value-based marketing approach and the